Patriotic Enthusiasm at the Beginning of the First World War - N. V. Yudin (Vestnik MGIMO-Universiteta, 2014)
In the present paper from the constructionist perspective is examined one of the most controversial issues of the modern western historiography of the First World War - the issue of patriotic enthusiasm of 1914, its scopes and nature. On the basis of a wide range of primary sources, including Russian and foreign archives, memoirs and letters of contemporaries the author carries out a comparative analysis of the response to the beginning of the war of urban and rural population of Great Britain, France and Russia. Against the backdrop of numerous patriotic demonstrations in large cities, the rural population's response looked much more constrained and passive. At the same time the latter attests rather to the peculiarities of rural culture than to the absence of patriotic upsurge. The author points out that besides apparent distinctions there was a lot of similarities in the urban and rural population's reaction to the beginning of the war. This refers to an immensely successful mobilization of continental armies, a rush of volunteers to the British army, and a drop of the labor movement in all European countries. The author comes to the conclusion that the patriotic upsurge in Europe in 1914 was not founded on a momentary outburst of chauvinism, but reflected a broad popular consensus on the war.